2016
DOI: 10.1039/c6nr01278g
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation oscillator-realized artificial electronic neurons, their responses, and noise

Abstract: A proof-of-concept relaxation oscillator-based leaky integrate-and-fire (ROLIF) neuron circuit is realized by using an amorphous chalcogenide-based threshold switch and non-ideal operational amplifier (op-amp). The proposed ROLIF neuron offers biologically plausible features such as analog-type encoding, signal amplification, unidirectional synaptic transmission, and Poisson noise. The synaptic transmission between pre- and postsynaptic neurons is achieved through a passive synapse (simple resistor). The synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…Reference [142] suggested that variability may be useful for stochastic computing, although this work used a threshold device. However, it is true that variability may be exploited for the development of useful systems, such as true random number generators and physical unclonable function devices for security applications.…”
Section: Variabilitymentioning
confidence: 99%
“…Reference [142] suggested that variability may be useful for stochastic computing, although this work used a threshold device. However, it is true that variability may be exploited for the development of useful systems, such as true random number generators and physical unclonable function devices for security applications.…”
Section: Variabilitymentioning
confidence: 99%
“…In PCM neurons, the as-made device consists of a nanoscale volume of phase-change material initially in the crystalline phase. [76,77] Threshold switching also occurs in RRAM devices, especially in the low operation voltage or current regime, and hence it can be exploited as volatile "turn-on" behavior, resembling the function of neurons. If the pulse is cut off abruptly, the molten part will rapidly quench into the amorphous phase following a glass transition.…”
Section: Threshold Switching In Artificial Neuronsmentioning
confidence: 99%
“…A CBA of resistance-based memory is perhaps most suitable for the MCHL algorithm, which emphasizes the benefits of the MCHL algorithm for efficient matrix calculation. 5,9,26 Given the stochasticity in resistance switching (particularly, on-and off-switching voltages 27,28 ) in nature, the probabilistic weight transition may be achieved by controlling driving voltage without RN generation 29 . Additionally, every update simply overwrites the current memory contents in this training scheme in that the past weight matrix no longer needs to be kept given the Markov chain nature, which also alleviates large memory needs.…”
Section: Discussionmentioning
confidence: 99%